Da TV para a Web 2.0: os novos usos do videoclipe // FROM TV TO WEB 2.0: THE NEW USES OF VIDEOCLIP - Zanetti, Daniela; Belo, Rafaela (Contemporanea, 2012)
Abstract: The article discusses aspects about the migration of music video from the television to Internet, paying attention to current configuration of the music industry and of the so-called independent or alternative markets of the music, and also the modes of pro- duction, circulation and consumption of music videos on Web 2.0. Resumo: O artigo aborda aspectos relativos à migração do videoclipe da TV para a Internet, atentando-se para a atual configuração da indústria fonográfica e dos chamados mercados alternativos ou independentes, e aos modos de produção, circulação e consumo de clipes musicais na Web 2.0.